Expression of the Drosophila gonadal gene: alternative promoters control the germ-line expression of monocistronic and bicistronic gene transcripts. - Schulz, R.A.; Miksch, J.L.; Xie, X.L.; Cornish, J.A.; Galewsky, S. (Development, 1990)
The Drosophila gonadal (gdl) gene is differentially expressed in the male and female germ lines. In males, expression in the gdlM mode results in a 1200-/1500-nucleotide RNA pair, whereas in females, expression in the gdlF mode results in a 1000-/1300-nucleotide RNA pair. Since the two expression modes are a result of alternative promoter usage, the sex-specific transcripts differ at their 5' ends. These sequence differences affect the coding capacity of the gene. A common open reading frame (ORF) of 193 codons (ORF193) is present in all four gdl transcripts; a consequence of the additional sequences at the 5' end of the gdlM transcripts is the presence of an additional ORF of 39 codons (ORF39). Translation of gdlF and gdlM cRNAs in a reticulocyte lysate reveals that these transcripts can serve as monocistronic and bicistronic mRNAs in vitro. An analysis of germ-line transformants harboring gdl-lacZ gene fusions provides information on gdl gene expression during gametogenesis. The fusion genes are transcribed and translated in the germ line; beta-galactosidase activity is detected in premeiotic and postmeiotic spermatogenic stages in males, and in nurse cells and oocytes of developing egg chambers in females. Both gdlM ORFs are used because transformant lines expressing the lacZ gene, fused in frame with either ORF39 or ORF193, are positive for beta-galactosidase activity in the testes. These studies also reveal that separable transcription control elements are responsible for gdl expression in the male and female germ lines.